PROJECT FINANCE MECHANISM FOR INVESTMENT PROJECT REALIZATION - V. V. Pereverzeva (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
This article focuses on project finance analysis, one of the most effective mechanisms to accumulate different financial resources in order to implement investment projects. Project finance is considered as a system, including multiple elements (participants, finance objects, contracts, risk management, infrastructure), which are in close relationship and provide financial flows effectiveness. Characteristics of project finance development current stage were identified. Project finance development current stage is focused on sustained economic growth, innovative development and global economy. It is shown that project finance system effective functioning is impossible without project risk management, identification and distribution of risks between project participants. A steady trend of deals and their costs annual increasing, decreasing in proportion of borrower`s own capital in total financial resource amount were identified and based on the global project finance market analysis. The factors affecting the project finance impact were defined: project management effective team presence, use of project management`s modern professional standards and technologies, establishment of communications system between project`s participants, project`s information and financial flows` transparency, use of qualified consultants and experts etc. It was considered that use of the project finance mechanism to implement innovative investment projects assumes particular importance during the establishment and development of digital economy.